Uji Aktivitas Antibakteri Ekstrak Cacing Tanah (Lumbricus Rubellus) Terhadap Bakteri Salmonella Thyphi Dan Staphylococcus Aureus Secara In Vitro - Mulyatno, Fitria Shirley Melinda, Dr. Retno Sintowati, M.Sc (2017)
Background: The use of earthworm to medicine for treating various diseases and to improve body endurance has long been known. Despite the advanced development of medical science, the use of earthworm is preferred by people because it has no side and toxic effects. Purpose: Purpose of the research to prove that the extract of earthworm (Lumbricus rubellus) is effectively inhibiting the growth of Salmonella thyphi and Staphylococcus aureus in vitro. Method of the research: The research is a laboratory experiment (true experiment) with posttest only control group designed to know antibacterial activity of earthworm (Lumbricus rubellus) extract. The antibacterial activity was examined by using well diffusion plate assay with concentrations of 10%, 25%, 50%, 75% and 100%. The well diffusion method was made in Muller Hinton media smeared with bacterial cultures of Salmonella thyphi and Staphylococcus aureus that had been standardized with 0.5 Mc Farland. Earthworm (Lumbricus rubellus) extract was dripped into the well with a series of concentrations and then, the cultures were incubated for 24 hours at 37oC and formation inhibition zone formed was measured by using vernier calipers. Results of the Research: The earthworm (Lumbricus rubellus) extracts started from concentration of 25%b/v - 100% b/v was proved to have potential to inhibit the growth of Salmonella thyphi and Staphylococcus aureus bacteria. It can be seen that an inhibition zones were formed in Salmonella thyphi culture for concentrations of 50%, 75% and 100% resulting on an averaged diameters of inhibition zones of 7,6±1,9mm, 8,5±1,3, 11,6±0,9mm respectively, and statistical test obtained p-value = 0.000 (p<0.05), whereas averaged inhibition zones for Staphylococcus aureus with extract concentrations of 50%, 75% and 100% were 3,9±0,6 mm, 4,8±1mm, 5,8mm±1,1mm, respectively, and statistical test obtained p-value = 0.000 (p<0.05). However, it was less effective than that of positive control. Conclusion: Earthworm (Lumbricus rubellus) extract has antibacterial activity against Salmonella thyphi at concentrations of 50%-100% and Staphylococcus aureus at concentrations of 25%-100% in vitro.